Antimony toxicity upon microorganisms from aerobic and anaerobic environments. Issue 1 (2nd January 2023) - Moreno-Andrade, Ivan; Sierra-Alvarez, Reyes; Pérez-Rangel, Marisol; Barrera, Cinthya; Field, Jim A.; Pat-Espadas, Aurora
Abstract: Antimony (Sb) is a toxic and carcinogenic metalloid that can be present in contaminated water generated by mining operations and other industrial activities. The toxicity of Sb (III) and Sb (V) to aerobic microorganisms remains limited and unexplored for anaerobic microorganisms involved in hydrogen (H2 ) and methane (CH4 ) production. This study aimed to evaluate the toxicity of Sb (III) and Sb (V) upon aerobic and anaerobic microorganisms important in biological wastewater treatment systems. Sb (III) was more toxic than Sb (V) independently of the test and environment evaluated. Under aerobic conditions maintained in the Microtox assay, Sb (V) was not toxic to Allivibrio fischeri at concentrations as high as 500 mg/L, whereas Sb (III) caused just over 50% inhibition at concentration of 250 mg/L after 5 min of exposure. In the respirometry test, for the specific oxygen uptake rate, the concentrations of Sb (III) and Sb (V) displaying 50% inhibition were 0.09 and 56.2 mg/L, respectively. Under anaerobic conditions, exposure to Sb (III) and Sb (V) led to a decrease in microorganisms activity of fermentative and methanogenic processes. The results confirm that the microbial toxicity of Sb depends on its speciation and Sb (III) displays a significantly higher inhibitory potential than Sb (V) in both aerobic and anaerobic environments.